The Milky Way, our galaxy - Lépine, Jacques (Cadernos de Astronomia, 2024)
We present the Milky Way, our Galaxy, first with an introduction of how we see it in the sky, and then with the history of the first steps of discovery, which led to the conclusion that the Galaxy is not the Universe itself, but just one among many galaxies. We describe its main components (galactic disk, spiral arms, bulge, bar), mentioning their dimensions and geometric shapes. We focus on the orbits of the stars, responsible for maintaining the shape of the components. We explain orbits based on the gravitational forces that act on stars.
Keywords: Milky Way; Structure of the Galaxy; Dynamics of the galaxy